Programa de educación ambiental para la gestión de residuos sólidos domésticos en el distrito de Casa Grande, Ascope - La Libertad - Leiva Cabrera, Frans Allinson (2021)
An Environmental Education Program has the functions of planning, diagnosis and application, it also includes the organizational structure, responsibility, process and resources to develop, implement, achieve and maintain the environmental policy in continuous improvement; Therefore, the management of solid waste is an activity that involves handling, conditioning, transporting, treatment, and finally their final disposal; Therefore, the investigation was carried out that aimed to develop an Environmental Education Program for the Management of Domestic Solid Waste in the District of Casa Grande - Ascope, La Libertad. Then through an evaluation of an initial Pretest on the collection of solid waste generated, which was obtained as an average of 100% ignorance in the four areas; To complete these results, waste samples were taken from each dwelling, as there was a high production of waste, causing a high level of pollution and environmental deterioration; For this reason, a member of each household was trained for four months, where didactic and audiovisual materials were used explained with a technical language, an evaluation (Knowledge Posttest) was taken, which obtained 100 % of people presented knowledge and applied the proper management of solid waste in the four study areas, consequently in the collection of solid waste generated (Posttest), there was a considerable decrease in solid waste applying the minimization, recycling and reuse processes, In the comparison of the Pretest and Posttest (Knowledge and solid waste generated), applying the paired “t” student test, it was shown that there is a significant difference; This allows us to conclude that it was evaluated that environmental education in the management of urban solid waste presented deficiencies, which improved with the program and training, positively influencing the management of domestic solid waste.